Protecting Creativity: Why Moral Rights Should be Extended to Sound Recordings under New Zealand Copyright Law - Wood, Nicholas Stuart (Victoria University of Wellington Law Review, 2001)
Traditionally, moral rights have not extended to the creators of sound recordings under either common law or civil law systems. The somewhat outdated rationale of this exclusion of sound recordings from the ambit of moral rights protection was generally that sound recordings were merely mechanical reproductions of already existing musical works, and hence the recordings lacked sufficient creativity to make them worthy of moral rights protection. In 1996, the WIPO Performances and Phonograms Treaty sought to remedy this anomaly in copyright law by extending the moral rights of paternity and of integrity to performers whose performances are fixed in sound recordings. This paper argues that New Zealand should follow WIPO's lead and extend the moral rights provisions of the Copyright Act 1994 to sound recordings. The author argues that sound recordings are imbued with sufficient creativity to merit moral rights protection and that this protection should be granted not only to performers but to sound engineers and producers, who also contribute creatively to the recording. This paper examines how moral rights in relation to sound recordings might work in practice and what remedies should be available for breach of these rights. The author concludes that the extension of moral rights to sound recordings need not impact detrimentally on the music industry, as some commentators fear.